Complete callosotomy in children with drop attacks; A retrospective monocentric study of 50 patients. (March 2022) - Ferrand-Sorbets, Sarah; Fohlen, Martine; Bourdillon, Pierre; Chipaux, Mathilde; Bulteau, Christine; Goetz, Laurent; Delalande, Olivier; Taussig, Delphine; Dorfmuller, Georg
Highlights: Corpus callosotomy is a palliative surgical procedure indicated in patients with bilateral drug-resistant epilepsy. Drop attacks are a frequent seizure type in children presenting with infantile spams and/or Lennox-Gastaut syndrome. Complete callosotomy is an effective and safe surgical treatment in patients with drop attacks. The improvement following callosotomy appears to be better in patients with tonic seizures. Abstract: Purpose: Corpus callosotomy is a palliative surgical procedure for patients with drug-resistant epilepsy and suffering from drop attacks, which are a source of major deterioration in quality of life and can be responsible for severe traumatic injury. The objective of this study is to identify clinical markers that would predict a better outcome in terms of drop attacks and other types of epileptic seizures. Methods: We reviewed a retrospective series of children who underwent complete corpus callosotomy at our institution, between January 1998 and February 2019. We analyzed the neurological and cognitive pre- and postoperative status, radiological datas, and electroencephalography (EEG) monitoring data. Results: Fifty children underwent a complete callosotomy at a mean age of 7.5 years. The median postoperative follow-up was 42.5 months. Forty-one patients (82%) had a favorable outcome, 29 (58%) of them becoming totally free of drop attacks. Statistical analysis of correlation between outcome of drop attacks and the characteristics of the patients did not find any trend in terms of age, etiology or developmental level. Regarding seizure types, the probability of being drop attack-free was significantly higher in case of tonic seizures (p = 0.017). Neurological complications occurred in two patients. A transient disconnection syndrome was observed in one child with good preoperative cognitive level. The mean hospital stay was short (5 -10 days). Conclusion: The results of this large monocentric case series with a long follow-up indicate that total callosotomy is a safe and effective treatment for children with drug-resistant epileptic drop attacks. Aside from a better surgical outcome for children with tonic seizures causing the falls, the lack of any other significant prognostic factor implies that no patient should a priori be excluded from this palliative surgical indication.